Abuso sexual infantil intrafamiliar e a escuta dos pediatras - Pavao, Maria Theresa [UNIFESP] (2011)
This research intends to analyze, through a qualitative approach and a case study, the narratives of Pediatricians from the basic health care service of Embu County and one specialized clinic in Sao Paulo County, with the purpose of learning how these professionals deal with the question of child sexual abuse. The data collection was made through non-participative observation techniques, semi-structured recorded interviews and registrations in a field notebook. The data were presented through the construction of narratives from the analysis of the recorded interviews following the orientation of Pope et al. (2009), which resulted in the construction of empiric axels, to be noted: a) the pediatricians facing the sexual abuse situation; b) ambiguity upon the notification; c) the necessity for finding physical signs and d) the question of ties with the patient and with the institution. The results show that sexual child abuse brings out emotional reactions in the professionals which harm the diagnostic objectiveness. On the other hand, they point out that bonding with patients helps better knowing them, thus allowing the detection of foul play, outthought most insist in finding evidence of physical signs of abuse. Despite all the training on sexual abuse which the majority of professionals go through, a common notion persists that when one notifies the suspicion of a case of abuse, it may cause not only personal, but also professional problems. We still point out that while the inefficiency of the law exists and considering the care demanded when a child enters the health care service, the importance of the sensitivity of the protective role exercised by these professionals at the moment they elect not to miss the opportunity of notification of suspicious or detected abuse cases, taking into consideration their co-responsibility for the continuation or not of the violence suffered by such child.